2012
DOI: 10.1016/j.jds.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of intentionally replanted molars according to preoperative locations of periapical lesions and the teeth

Abstract: Background/purpose: The aims of this retrospective study were to assess the influence of preoperative periapical lesions on the healing of intentionally replanted teeth and compare outcomes of intentional replantation (IR) between maxillary and mandibular molars. Materials and methods: In this study, we retrospectively analyzed 79 cases in whom the IR procedure was used. The outcome of treatment was classified clinically and radiographically as either success or failure. Results: The overall success rate of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…, Cho & Lee , Lee et al . ). However, during this time, orthodontic treatment continued on the remaining dentition, but without applying force on the transplanted tooth until 3 months of healing period (Tatli et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Cho & Lee , Lee et al . ). However, during this time, orthodontic treatment continued on the remaining dentition, but without applying force on the transplanted tooth until 3 months of healing period (Tatli et al .…”
Section: Discussionmentioning
confidence: 97%
“…Another study has shown lower success rate of IR on maxillary molar as compared with mandibular molar (10). The authors of the study speculated that gravity might influence negatively on the reattachment on the replanted tooth, which increased the mobility of the tooth and thus reduced the treatment outcome (10).…”
Section: Discussionmentioning
confidence: 99%
“…21), que consisten en una extracción mínimamente traumática (daño mínimo en los tejidos y hueso circundante), el conocimiento de la anatomía apical, tiempo extraoral corto con visión e iluminación adecuadas (con la ayuda del microscopio óptico dental si es posible), un correcto sellado apical y el cuidado posoperatorio por parte del paciente. La biocompatibilidad del material de obturación también afectará al proceso de curación periapical (8,15,19,26).…”
Section: Discussionunclassified